Analisis Pengaruh Likuiditas dan Pertumbuhan Penjualan Terhadap Kebijakan Utang - Susanti, Susanti; Annisa, Mutiara Lusiana (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The aim of the research is to determine the effect of liquidity and sales growth on debt policy. The population in the research are manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the 2021-2022 period which operate in the advertising, printing and media sectors. The type of sampling used in this research is purposive sampling. The companies that were the objects of research were 16 companies over 2 periods (2021-2022), namely Mahaka Media Tbk, Elang Mahkota Teknologi Tbk, MD Pictures Tbk, Fortune Indonesia Tbk, Jasundo Tiga Perkasa Tbk, First Media Tbk, Link Net Tbk, Star Pacific Tbk, Mahaka Radio Integra Tbk, Intermedia Capital Tbk, Media Nusantara Citra Tbk, MNC Studios International Tbk, MNC Sky Vision Tbk, Surta Citra Media Tbk, Tempo Inti Media Tbk, and Visi Media Asia Tbk. The research results show that liquidity and sales growth influence debt policy. Liquidity can have a negative effect on a company's debt policy. Meanwhile, sales growth has a positive effect on debt policy. Liquidity refers to a company's ability to meet its short-term financial obligations. A liquid company has enough liquid assets or access to financial resources to pay its short-term obligations and tends to reduce its debt. Furthermore, strong sales growth can increase the company's cash flow. With higher cash flow, a company may have more internal sources of funds to fund investments and capital needs. Apart from that, good sales growth makes it easier for companies to get loans with lower interest rates because they are considered to have lower risks.